TOP1 modulation during melanoma progression and in adaptative resistance to BRAF and MEK inhibitors. (November 2021) - Oliveira, Érica Aparecida de; Chauhan, Jagat; Silva, Julia Rezende da; Carvalho, Larissa Anastacio da Costa; Dias, Diogo; Carvalho, Danielle Gonçalves de; Watanabe, Luis Roberto Masao; Rebecca, Vito W.; Mills, Gordon; Lu, Yiling; da Silva, Aloisio Souza Felipe; Consolaro, Márcia Edilaine Lopes; et al.
Abstract: In melanomas, therapy resistance can arise due to a combination of genetic, epigenetic and phenotypic mechanisms. Due to its crucial role in DNA supercoil relaxation, TOP1 is often considered an essential chemotherapeutic target in cancer. However, how TOP1 expression and activity might differ in therapy sensitive versus resistant cell types is unknown. Here we show that TOP1 expression is increased in metastatic melanoma and correlates with an invasive gene expression signature. More specifically, TOP1 expression is highest in cells with the lowest expression of MITF, a key regulator of melanoma biology. Notably, TOP1 and DNA Single-Strand Break Repair genes are downregulated in BRAFi- and BRAFi/MEKi-resistant cells and TOP1 inhibition decreases invasion markers only in BRAFi/MEKi-resistant cells. Thus, we show three different phenotypes related to TOP1 levels: i) non-malignant cells with low TOP1 levels; ii) metastatic cells with high TOP1 levels and high invasiveness; and iii) BRAFi- and BRAFi/MEKi-resistant cells with low TOP1 levels and high invasiveness. Together, these results highlight the potential role of TOP1 in melanoma progression and resistance. Graphical Abstract: ga1